A theorem on continuum of the projector optimal behaviors in antagonistic model of building resources distribution under segment uncertainties with incorrectly pre-evaluated one left and one right endpoints - Romanuke, V.V. (Problems of Tribology, 2014)
There is considered a problem of distributing optimally the four-mounted building resources under uncertainties. The theorem on continuum of the projector optimal strategies in the antagonistic model with a left endpoint and a right endpoint of segment uncertainties, been pre-evaluated incorrectly, has been proved.